2018
DOI: 10.1152/ajpgi.00094.2017
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt: impact on systemic hemodynamics and renal and cardiac function in patients with cirrhosis

Abstract: Transjugular intrahepatic portosystemic shunt (TIPS) alleviates portal hypertension and possibly increases central blood volume (CBV). Moreover, renal function often improves; however, its effects on cardiac function are unclear. The aims of our study were to examine the effects of TIPS on hemodynamics and renal and cardiac function in patients with cirrhosis. In 25 cirrhotic patients, we analyzed systemic, cardiac, and splanchnic hemodynamics by catheterization of the liver veins and right heart chambers befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 54 publications
2
45
0
2
Order By: Relevance
“…As already mentioned, LV contractility appears to be decreased in patients with cirrhosis, whereas the lack of response of LV contractility to hemodynamic changes might be the reason for development of ascites and decompensation . In one elaborate, invasive, pathophysiologic, but small study in patients with TIPS, profound changes were induced in cardiac contractility after TIPS, which could only be reflected noninvasively by speckle tracking . Our present study confirms that the most suitable, noninvasive, and less biased technique seems to be STE, while it describes for the first time LV‐GLS as the best predictor of ACLF development and mortality.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As already mentioned, LV contractility appears to be decreased in patients with cirrhosis, whereas the lack of response of LV contractility to hemodynamic changes might be the reason for development of ascites and decompensation . In one elaborate, invasive, pathophysiologic, but small study in patients with TIPS, profound changes were induced in cardiac contractility after TIPS, which could only be reflected noninvasively by speckle tracking . Our present study confirms that the most suitable, noninvasive, and less biased technique seems to be STE, while it describes for the first time LV‐GLS as the best predictor of ACLF development and mortality.…”
Section: Discussionsupporting
confidence: 80%
“…Insertion of a transjugular intrahepatic portosystemic shunt (TIPS) induces a prompt decompression of the portal venous system and effectively treats complications of portal hypertension; however, careful selection of patients is required . TIPS insertion increases central blood volume despite a severe aggravation of preload . These changes increase cardiac workload and encroach on cardiac reserves, which are especially decreased in patients with decompensated cirrhosis .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…65 The fre-quently used ejection fraction in resting does not identify patients who might fail after TIPS. 65 Recently, two published pathophysiological prospective studies 66,67 in humans by the group of S. Møller and F. Bendtsen demonstrated an increase in cardiac output in TIPS as well as an increase in stroke volume to increase the central blood volume. However, the authors also found an inability to increase the heart rate in response to a hemodynamic challenge after TIPS.…”
Section: Selection Of Patients and Timing For Tipsmentioning
confidence: 99%
“…There is avid evidence on the salutary impact of TIPS on renal function, including improved urinary sodium excretion (indicative of ameliorated renal perfusion) as well as an increase in clearance of creatinine [22]. Based on recent data, cardiorenal interplay is the key mediator of the beneficial renal effects of TIPS, as it significantly enhances cardiac inotropy, leading to increased central blood volume and renal perfusion [23]. Furthermore, the benefits of TIPS could partly be explained by improvement in endothelial function that follows mitigation of systemic inflammation through lowering pressures and shear stress in the portal system and hindering of the intestinal translocation of bacteria.…”
Section: Cardiorenal Interactions After Portosystemic Shuntingmentioning
confidence: 99%